Supervisory Board and Company Borrowing: The Case of Developing Economics - Ilona, Desi; Zaitul, Zaitul; Ethika, Ethika (Journal of Reviews on Global Economics, 2019)
The objective of this paper is to find out the effects of the independence and size of the supervisory board on company borrowing in a two-tier board system. Unlike prior studies, such as in the United States, the current study is conducted in a developing country that has adapted a Continental European System. This study uses panel data analysis for 1,981 observations of 283 Indonesian listed companies in the 2004-2010 period. The control variables are Return on Assets (ROA), quality of audit, age, size and firm growth. Before panel data analysis is run, the outlier and normality tests are used. In addition, test of random-effect or fixed-effect model is conducted. This work finds that supervisory board independence has a negative effect on company borrowing. Further, firm profitability has a consistent effect on company borrowing.